If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 1) = 4(x + -3) Reorder the terms: (1 + 2x) = 4(x + -3) Remove parenthesis around (1 + 2x) 1 + 2x = 4(x + -3) Reorder the terms: 1 + 2x = 4(-3 + x) 1 + 2x = (-3 * 4 + x * 4) 1 + 2x = (-12 + 4x) Solving 1 + 2x = -12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 1 + 2x + -4x = -12 + 4x + -4x Combine like terms: 2x + -4x = -2x 1 + -2x = -12 + 4x + -4x Combine like terms: 4x + -4x = 0 1 + -2x = -12 + 0 1 + -2x = -12 Add '-1' to each side of the equation. 1 + -1 + -2x = -12 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = -12 + -1 -2x = -12 + -1 Combine like terms: -12 + -1 = -13 -2x = -13 Divide each side by '-2'. x = 6.5 Simplifying x = 6.5
| 32+5r=-8(-1-r) | | 17g-16g+1=14 | | 7x+1-4x=4x-5+1 | | 2(-5/2)^2-(-5/2)-15 | | 6x+4y=3x-8 | | j-13=46 | | 3y*2+5*2=5y*3 | | 34x+3=45 | | P+.15p=23 | | 8(n-5)=-47+8n | | 5x+4=2(X+11) | | 6+3i= | | -4(j+14)=-12 | | 17-9(.8)=3+12.8 | | x+x(0.13)=200 | | y=0.15x+40 | | -1+10x=-81 | | 6x^2=5-13x | | (11)7X(11)6= | | 3(m-14)=6 | | 4/20x=10/20 | | -18÷2/3 | | 2x+8=4x+3-2x+5 | | 15w-14w-1=6 | | 1-x=-4 | | 3(y-10)+1=-33(y-8) | | 7x+36=x | | 1+x+1-9=x-7 | | 32.7=2*pi*r | | 3r+20r-(-12)=-11 | | 2/6(4x-1) | | x+x(0.13)=1200 |